2022
DOI: 10.3389/fpubh.2022.857368
|View full text |Cite
|
Sign up to set email alerts
|

Association of Blood Glucose Level and Glycemic Variability With Mortality in Sepsis Patients During ICU Hospitalization

Abstract: BackgroundThere was considerable debate regarding the effect of mean blood glucose (MBG) and glycemic variability (GV) on the mortality of septic patients. This retrospective cohort study aimed to assess the association between MBG and GV with ICU mortality of sepsis patients and to explore the optimal MBG range.MethodsSepsis patients were enrolled from the Medical Information Mart for Intensive Care IV database (MIMIC-IV). MBG and glycemic coefficient of variation (GluCV) were, respectively, calculated to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…The metabolic changes that cause hyperglycemia include muscle glycolysis and lipolysis, followed by hepatic glycogenesis and glycolysis ( Hirasawa et al, 2009 ; Ferreira et al, 2022 ). Among patients with Sepsis, variability in blood glucose levels is associated with higher mortality rates ( Ali et al, 2008 ; Lu et al, 2022 ). In addition to insulin resistance, metabolic dysfunction is also correlated with the MetS ( Marette et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic changes that cause hyperglycemia include muscle glycolysis and lipolysis, followed by hepatic glycogenesis and glycolysis ( Hirasawa et al, 2009 ; Ferreira et al, 2022 ). Among patients with Sepsis, variability in blood glucose levels is associated with higher mortality rates ( Ali et al, 2008 ; Lu et al, 2022 ). In addition to insulin resistance, metabolic dysfunction is also correlated with the MetS ( Marette et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…A mild elevation of glucose is acceptable because it allows the host to survive during severe stress. However, an excessively high level of glucose may cause immunosuppression and oxidative stress, which were associated with worse outcomes [ 25 , 26 ]. Serum creatinine is the most widely used measure of renal function in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between increased RDW and increased glycosylated hemoglobin (HbA1c) levels, which re ects the magnitude of glycemic variability in patients with diabetes. Furthermore, these studies reported that hyperglycemia shortens the lifespan of red blood cells, leading to a highly variable red blood cell volume or RDW, which is associated with increased mortality [22][23][24][25]. In addition, RDW is associated with the development of diabetes-related complications.…”
Section: Discussionmentioning
confidence: 99%